РОЗРАХУНОК ВИХРОВИХ СТРУМІВ У ТРИФАЗНОМ ТЕПЛОГЕНЕРАТОРІ ІНДУКЦІЙНОГО ТИПУ З ВИКОРИСТАННЯМ МЕТОДУ ВТОРИННИХ ДЖЕРЕЛ. РЕЖИМ СТРУМУ - Жильцов, А.В.; Заєць, Н.А.; Березюк, А.О.; Гай, О.В.; Ликтей, В.В. (Інститут електродинаміки НАН України, Київ, 2023)
Using the secondary sources method, a three-dimensional mathematical model of a heat induction type generator was developed when it is powered by a three-phase current source with a load in the form of non-connected ferromagnetic conducting pipes, taking into account the symmetrical distribution of the densities of the electromagnetic field secondary sources. The analysis of the secondary sources distribution of the electromagnetic field and heat losses in the loaded one allowed us to conclude about the possibility of neglecting the components of eddy current densities and magnetization current densities along the symmetry axis of the pipes and in the radial direction, which reduces the number of secondary source densities sought from six to three. It is shown that for the analysis of electromagnetic processes in heat generators of this type, it is permissible to assume the uniformity of the secondary sources density distribution in all pipes, which, when using the method of secondary sources, makes it possible to reduce the search area to one ferromagnetic base pipe. References 8, figures 3, table 1.